Ciencia e investigación agraria 2018
DOI: 10.7764/rcia.v45i3.1962
|View full text |Cite
|
Sign up to set email alerts
|

Resistance inducers and biochemical mechanisms in the control of anthracnose in cowpea

Abstract: J. M. Silva, M. B. C. L. Medeiros, J. T. C. Oliveira, E. V. Medeiros, C. M. Souza-Motta, and K. A. Moreira. 2018. Resistance inducers and biochemical mechanisms in the control anthracnosis on cowpea. Cien. Inv. Agr. 45(3): 290-300. Different responses are observed in plants after infection by pathogens. The usage of systemic inducers, whether biotic or abiotic,has the function to increase the enzymatic production of the plant defense system. In that sense, our present research aims to evaluate the disease seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…In a previous study, acibenzolar-S-methyl significantly reduced OLS severity by an average of 48-68% compared to the untreated control [8]. Numerous previous studies have shown that ASM is a potent inhibitor of diseases caused by both fungal and bacterial pathogens on several hosts [30][31][32]. The increased resistance of ASM-treated plants has been associated with a higher activation rate of principal antioxidant enzymes, such as peroxidase, superoxide dismutase, catalase and ascorbate peroxidase, an enhancement of polygalacturonase-inhibiting proteins, and the increased production of PR-proteins [13].…”
Section: Discussionmentioning
confidence: 89%
“…In a previous study, acibenzolar-S-methyl significantly reduced OLS severity by an average of 48-68% compared to the untreated control [8]. Numerous previous studies have shown that ASM is a potent inhibitor of diseases caused by both fungal and bacterial pathogens on several hosts [30][31][32]. The increased resistance of ASM-treated plants has been associated with a higher activation rate of principal antioxidant enzymes, such as peroxidase, superoxide dismutase, catalase and ascorbate peroxidase, an enhancement of polygalacturonase-inhibiting proteins, and the increased production of PR-proteins [13].…”
Section: Discussionmentioning
confidence: 89%
“…To mitigate the adverse effects of fungicides on humans and the environment, chemical elicitors have been explored as an alternative approach for managing diseases caused by Colletotrichum spp. across various plant hosts (Arora, 2013;Li et al, 2016;da Silva et al, 2018). Therefore, the objectives of this study were: a, to assess the impact of boric acid, ascorbic acid, and salicylic acid on the linear growth and sporulation of C. orbiculare and C. acutatum in cucumber and pepper plants under in vitro conditions; b, to evaluate the activity of oxidative enzymes and total phenolic compounds to elucidate the potential correlation between their activity and the induced defense mechanisms; c. to analyze micrographs obtained through scanning electron microscopy (SEM) to examine the effects of salicylic acid on C. orbiculare and C. acutatum; d, to investigate the effectiveness of salicylic acid in controlling anthracnose in cucumber and pepper plants under glasshouse condition.…”
Section: Introductionmentioning
confidence: 99%